Retinoblastoma from human stem cell-derived retinal organoids - Jackie L. Norrie; Anjana Nityanandam; Karen Lai; Xiang Chen; Matthew Wilson; Elizabeth Stewart; Lyra Griffiths; Hongjian Jin; Gang Wu; Brent Orr; Quynh Tran; Sariah Allen; et al. (Nature Communications, 2021)
Retinoblastoma is a heritable pediatric cancer driven by mutations in RB1. Here, the authors demonstrate the first patient derived model of retinoblastoma using iPSCs from patients with germline mutations in RB1.